Distinct domains of the AVRPM3A2/F2 avirulence protein from wheat powdery mildew are involved in immune receptor recognition and putative effector function. Issue 2 (17th February 2018) - McNally, Kaitlin Elyse; Menardo, Fabrizio; Lüthi, Linda; Praz, Coraline Rosalie; Müller, Marion Claudia; Kunz, Lukas; Ben‐David, Roi; Chandrasekhar, Kottakota; Dinoor, Amos; Cowger, Christina; Meyers, Emily; Xue, Mingfeng; et al.
Summary: Recognition of the AVRPM3 A2/F2 avirulence protein from powdery mildew by the wheat PM3A/F immune receptor induces a hypersensitive response after co‐expression in Nicotiana benthamiana . The molecular determinants of this interaction and how they shape natural AvrPm3 a2/f2 allelic diversity are unknown. We sequenced the AvrPm3 a2/f2 gene in a worldwide collection of 272 mildew isolates. Using the natural polymorphisms of AvrPm3 a2/f2 as well as sequence information from related gene family members, we tested 85 single‐residue‐altered AVRPM3 A2/F2 variants with PM3A, PM3F and PM3F L 456P/Y458H (modified for improved signaling) in Nicotiana benthamiana for effects on recognition. An intact AvrPm3 a2/f2 gene was found in all analyzed isolates and the protein variant recognized by PM3A/F occurred globally at high frequencies. Single‐residue alterations in AVRPM3 A2/F2 mostly disrupted, but occasionally enhanced, the recognition response by PM3A, PM3F and PM3F L 456P/Y458H . Residues enhancing hypersensitive responses constituted a protein domain separate from both naturally occurring polymorphisms and positively selected residues of the gene family. These results demonstrate the utility of using gene family sequence diversity to screen residues for their role in recognition. This approach identified a putative interaction surface in AVRPM3 A2/F2 not polymorphic in natural alleles. We conclude that molecular mechanisms besides recognition drive AvrPm3 a2/f2 diversification.